3D Bioprinting and the Future of Surgery - Jovic, Thomas H.; Combellack, Emman J.; Jessop, Zita M.; Whitaker, Iain S. (Frontiers in Surgery, 2020)
Introduction: The disciplines of 3D bioprinting and surgery have witnessed incremental transformations over the last century. 3D bioprinting is a convergence of biology and engineering technologies, mirroring the clinical need to produce viable biological tissue through advancements in printing, regenerative medicine and materials science. To outline the current and future challenges of 3D bioprinting technology in surgery Methods: A comprehensive literature search was undertaken using the MEDLINE, EMBASE and Google Scholar databases between 2000 and 2019. A narrative synthesis of the resulting literature was produced to discuss 3D bioprinting, current and future challenges, the role in personalised medicine and transplantation surgery and the global 3D bioprinting market. Results: The next 20 years will see the advent of bioprinted implants for surgical use, however the path to clinical incorporation will be fraught with an array of ethical, regulatory and technical challenges of which each must be surmounted. Previous clinical cases where regulatory processes have been bypassed have led to poor outcomes and controversy. Speculated roles of 3D bioprinting in surgery include the production of de novo organs for transplantation and use of autologous cellular material for personalised medicine. The promise of these technologies has sparked an industrial revolution, leading to an exponential growth of the 3D bioprinting market worth billions of dollars. Conclusion: Effective translation requires the input of scientists, engineers, clinicians and regulatory bodies: there is a need for a collaborative effort to translate this impactful technology into a real-world healthcare setting and potentially transform the future of surgery.